Characterization of Free Sugars in Hawthorn (Crataegus spp.) Species - FIKRET BALTA, M.; YORUK, I.H.; ASKIN, M.A.; YARILGAC, T.; KAZANKAYA, A. (Asian Journal of Chemistry, 2010)
Free sugar contents were detected by HPLC in the fruits of 20 genotypes belonging to 5 different species (Crataegus spp.) collected from Malatya (eastern Turkey). The fresh fruits of C. orientalis, C. aronia, C. meyeri, C. tanacetifolia and C. pontica contain in average 1.36- 1.84 g/100 g sucrose, 4.18-5.33 g/100 g fructose, 0.42-1.12 g/100g maltose and 2.58-3.62 g/100 g glucose, respectively. The contents of sucrose, fructose, maltose and glucose did not differ by the species statistically. The main sugar was fructose in all hawthorn species, followed by glucose, sucrose and maltose. The mean percentages of fructose, glucose, sucrose and maltose within the total amount of these 4 sugars were 47.9, 29.4, 15.2 and 7.4 %, respectively. In addition, the species averagely had soluble solids content (SSC) 13.6-17.6 %.